The emerging application of ultrasound in lactose crystallisation - Zamanipoor, Mohammad; Mancera, Ricardo (Elsevier, 2014)
Ultrasonic processing is the industrial application of sound waves with a frequency above the upper limit of human hearing. Interest has arisen recently in the effects of ultrasound on the crystallisation of lactose as an innovative technology to improve its recovery and the control over its crystal properties. This not only will increase the financial profit for lactose manufacturers and improve the quality of lactose for specific applications, but will also improve the quality of end products manufactured with lactose as an ingredient.